Evaluation of monorail haulage systems in metalliferous underground mining - Besa, Bunda (Curtin University, 2010)
The decline is a major excavation in metalliferous mining since it provides the main means of access to the underground and serves as a haulage route for underground trucks. However, conventional mining of the decline to access the ore body poses economic and technical challenges that require innovative responses. The average cross-sectional area of mine declines in Australia is 5m wide x 5m high. The large excavations associated with current underground mining practices are economically and geotechnically inappropriate, especially for narrow vein mining conditions. The decline gradient of 1 in 7 (8[superscript]o) designed to accommodate truck haulage results in a significantly longer decline compared to a decline mined at a steeper gradient. Further, the current drill-blast-load-haul cycle does not allow rapid development of the decline to access the ore body since the cycle is made up of discontinuous segments. The use of diesel equipment poses health risks and increases ventilation requirements. The heat load and air borne exhaust contaminants emitted by large diesel engines create heavy demand on mine ventilation, sometimes resulting in substandard working conditions. As mines get deeper, there is a tendency to increase the truck and loader fleet – which results in traffic congestion in the decline. Metal prices in the recent boom may have helped to offset some of the shortcomings of current practices, and although the good times may continue, a down-turn could find many operations exposed. Federal government emissions trading scheme encourage mining companies to reduce carbon emissions in their operations.This study was prompted by the need to investigate the potential of the monorail haulage system in metalliferous mining, particularly in decline development and main haulage in view of shortcomings of the current practices. Monorail systems are being used in mines around the world for material transport and man-riding but their utility in rock transport has not been fully investigated. Hence, it is proposed to replace non-shaft component of the mine haulage system with roof/back mounted monorail technology using continuous conductor technology to provide competitive haulage rates in substantially smaller excavations at steeper gradient than is currently achievable. It is proposed that a suite of equipment can be adapted or modified to enable development of the decline supported by the monorail system.To this end, a drill system mounted on the monorail accompanied by a pneumatic system for loading rock into monorail containers is proposed. The proposed decline gradient for the monorail decline is 1 in 3 (or 20[superscript]0) with a cross-sectional area of 4m wide x 4m high. Decline dimensions of size 4.0m x 4.0m (minimum opening for monorail system is 3m x 3m) are used in this design in order to leave enough working space (underneath and on the sidewalls) and to accommodate other mine services, such as, ventilation tubing, air and water pipes and cables. Systems analysis, engineering economics and computer simulation are used to evaluate the feasibility of the monorail mining system for decline development. Technical data relating to the operation of monorail systems in underground mining was obtained from Solutions for Mining Transport (SMT) – Scharf, of Germany, a company that manufactures monorail systems. Monorail haulage has definite advantages over conventional haulage; these include the use of electrical power instead of diesel, steeper gradients (up to 36[superscript]0), smaller excavations, tighter horizontal and vertical turning radii and potential for automation. The concepts are applied to a narrow vein ore deposit with results indicating that the monorail system delivers significant savings in terms of time and cost of decline development in this specific application.Stability of the monorail drilling system is critical in ensuring high performance of the drilling system. Stabilisation of the system requires determination of the horizontal, vertical and lateral forces of the system. According to the findings, these forces depend on the vector position of the two drilling booms that will be mounted onto the monorail train. Therefore, the research provides minimum and maximum monorail system reaction forces in horizontal and vertical stabilisers that will stabilise the system during drilling operations. Because of the configuration and positioning of the monorail drilling system, the research has also shown that with appropriate swing angles and lifting angles that will enable the system to reach the whole drill face during drilling operations.Since pneumatic or suction system is used during loading process, the research has revealed that the density of rock fragments, rock fragmentation, conveying air velocity and the negative pressure of the system would greatly influence the loading time and power consumption of the system. Therefore, the study has determined optimum fragmentation of the pneumatic system for various conveying air velocities. Additionally, for the efficient operations of the system, a range of conveying air velocities that give optimal mass flow rate (mass flow rate that give shorter loading time) and optimal power consumption have been determined at maximum negative pressure of 60kPa (0.6 bars).Since the monorail drilling and loading systems move on the rail/monorail installed in the roof of the decline and supported by roof bolts, suspension chains and steel supports, the strength of the support system is critical. To avoid system failure, it is imperative that the force in each roof bolt, suspension chain and steel support capable of suspending the weight of the heaviest component of the system is determined. Through the models developed, this study has determined the minimum required strength of roof bolts, suspension chains and steel supports that can suspend and support the components of the drilling and loading systems.To increase the efficiency and improve the safety of the two systems, the automation design for monorail drilling and loading systems’ processes have been developed. The proposed automation system would increase productivity by improving operator performance through control of the two systems’ processes. It is hoped that automation of the monorail drilling and loading systems will reduce the total drill-load-haul cycle time hence improving the efficiency of the systems.The application of simulation techniques was deemed useful to determine the performance of the monorail system in mining operations. During modelling, a simulation programme was written using General Purpose Simulation System (GPSS/H) software and results of the simulation study were viewed and examined in PROOF animation software. According to simulation results, the monorail system will have the same advance rate as conventional method since both systems have one blast per shift. However, the total drill-blast-load-haul cycle time for the monorail system is lower than for conventional method.Since the monorail system poses health and safety challenges during operations, through risk analysis, this study has identified root factors that have the potential to cause monorail system risk and hazard failure. The research has revealed that lack of maintenance of the monorail system and the monorail installations, production pressure and insufficient training of personnel on monorail system use are the major root factors that have the potential to cause risk and hazard failure. In order to improve the health and safety of the system, the study has suggested risk and hazard control strategies which are aimed at reducing the level of risk by directing corrective measures at potential root causes as opposed to addressing the immediate obvious symptoms such as monorail falling from support system, monorail running out of control, and others.A mine design case study using a monorail technology was conducted using one of ‘South Deeps’ gold deposits of Jundee mine operations (owned by Newmont Mining Corporations). Nexus deposit, one of ‘South Deeps’ deposits, was selected as case study area. The case study indicates that development of decline access to Nexus deposits using monorail technology is feasible. Compared with conventional decline development, results have shown that the monorail system has the potential of reducing the decline length to Nexus deposits by over 62.6% and decline costs by 63% (i.e., spiral decline and straight incline from the portal only). Furthermore, the study indicates that with the monorail system, there is a potential of reducing the total capital development costs to Nexus deposit by 22% (i.e., cost of developing the spiral decline, straight incline from the portal, crosscuts, ventilation network and installation and purchase of monorail train). Also, due to shorter decline length coupled with smaller decline openings, the duration of decline development reduces by 71.8%.